North America, British possessions - Lizars, Daniel , 1793–1875 (Cartographer)
Map of Canada and surrounding areas of United States, Greenland, Alaska, and Iceland. Based off of many previous maps with references. Shows waterways, contours, boundaries, place names, and anglicized names of many First Nations groups. Scale 1:13,000,000. Relief shown by hachures. Nippissing Lake in the shape of a W. Original publication : The Edinburgh geographical and historical atlas, comprehending a sketch of the history of geography . and history of each continent, state, and kingdom, delineated. And a tabular view of the principal mountain chains in the World. Engraved on sixty-nine copperplates, and compiled from materials drawn from the newest and most authentic sources. Edinburgh: Published by John Hamilton, 15, South St. Andrew Street, successor to Daniel Lizars; Whittaker, Treacher, & Co., Ave-Maria Lane, London; and W. Curry, Jun. & Co., Dublin. (1831?) Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .